Innovation and the Entrepreneurial University (Science, Technology and Innovation Studies,, 2018)
The book explores different approaches towards the 'entrepreneurial university' paradigm, explores channels and mechanism used by universities to implement the paradigm and contributes to the public discussion on the impact of commercialization on university research and knowledge. It argues that different types of university-industry interaction may have repercussions even on funding of basic research if an appropriate balance is ensured between the two. University activities - both research and education in all forms - should provide economic and social relevance directed towards open science and open innovation. This book adds value to current knowledge by presenting both a conceptual framework and case studies which describe different contexts.